GRAMMATIC TRANSFORMATION IN THE PROCESS OF TRANSLATION AND THEIR ORIGIN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article focuses on grammatic changes in the example of Daniel Defoe’s The Life and Adventures of Robinson Crusoe. Examples given in two languages throughout the article allow understanding the new types of stylistic transformation.